1997
DOI: 10.1093/humrep/12.4.780
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-related chromosome abnormalities in human embryos

Abstract: Mosaicism was studied in good quality embryos from four different centres in order to assess the effects of follicular induction and exposure to laboratory conditions on chromosomal status. The donated embryos were fully biopsied and analysed by fluorescence in-situ hybridization using probes for chromosomes X, Y, 13, 18 and 21, simultaneously. The number of abnormal cells present indicated the division at which mosaicism first occurred (4/4 cells at first division, 2/4 cells at second, 2/8 at third). The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(119 citation statements)
references
References 7 publications
7
107
2
1
Order By: Relevance
“…The increased number of abnormal embryos was mainly due to a higher incidence of mitotic segregation errors, leading to mosaicism. These findings supported both previous reports of an association between ovarian stimulation regimens and chromosomal mosaicism in human embryos (Munne et al 1997), as well as reports indicating an association between meiotic and mitotic chromosome 21 cell division errors with significantly higher FSH doses daily (Katz-Jaffe et al 2005). Thus, milder ovarian stimulation regimens seem to be less detrimental to the vulnerable process of nuclear maturation and chromosomal segregation.…”
Section: Does Ovarian Stimulation Disrupt Chromosomal Competence Of Tsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased number of abnormal embryos was mainly due to a higher incidence of mitotic segregation errors, leading to mosaicism. These findings supported both previous reports of an association between ovarian stimulation regimens and chromosomal mosaicism in human embryos (Munne et al 1997), as well as reports indicating an association between meiotic and mitotic chromosome 21 cell division errors with significantly higher FSH doses daily (Katz-Jaffe et al 2005). Thus, milder ovarian stimulation regimens seem to be less detrimental to the vulnerable process of nuclear maturation and chromosomal segregation.…”
Section: Does Ovarian Stimulation Disrupt Chromosomal Competence Of Tsupporting
confidence: 90%
“…Although advanced maternal age is the only clearly identified risk factor for chromosomal aneuploidy in the human embryo (Hassold & Hunt 2001, Champion & Hawley 2002, a number of studies have reported particularly high rates of chromosomal aneuploidy and mosaicism in early human IVF embryos (Munne et al 1997, Katz-Jaffe et al 2005, Baart et al 2007. Recently, post-zygotic chromosome instability has been observed to be a common feature of early human embryogenesis, leading to chromosomal disorders such as mosaicism and uniparental disomies in the majority of cleavagestage embryos (Vanneste et al 2009).…”
Section: Does Ovarian Stimulation Disrupt Chromosomal Competence Of Tmentioning
confidence: 99%
“…There is growing evidence in animal studies to support the hypothesis that elevated FSH is an underlying cause of embryo defects [9,10,39]. However, whereas animal studies seem to support an association between FSH exposure and embryonic defects, human studies have been more inconsistent [25,26,31,37,45]. In our study, the FSH dose and the number of retrieved oocytes had a negative impact on the TE quality.…”
Section: Discussioncontrasting
confidence: 53%
“…Some of these abnormalities can be morphological [2,3] or chromosomal [4]. Preliminary observations suggest that aneuploidy in embryos may not only be affected by maternal age [5], but also by the ovarian stimulation regimens employed in IVF [6]. A large prospective study used preimplantation genetic screening to analyse the effects of mild versus conventional stimulation on chromosome segregation behaviour during meiosis [7].…”
Section: Introductionmentioning
confidence: 99%